Programa cuentos infantiles peruanos para fomentar el hábito lector en estudiantes de 4 años, de la I.E 1591, Trujillo, 2018 - Vasquez Cango, Fabiola Marisol (2019)
In the thesis entitled: Program peruvian children's tales to promote the reading habit in students of 4 years, of the I.E. 1591 - Trujillo, 2018. Its purpose is to show how Peruvian children's stories allow to promote the reading habit in preschool students, since due to lack of strategies on the part of classroom teachers it is not developed in an adequate manner._x000D_ The research is pre experimental type, formed by a group, which is the experimental group, this group is formed by the classroom of 4 years A, which was applied the pretest to identify their level of reading habit. Subsequently, the program based on Peruvian children's stories was administered, and at the end of this, the post test was applied, the results obtained show us that the program "Peruvian children's stories" significantly encouraged the reading habit in the children of the experimental group